A course in weight loss : 21 spiritual lessons for surrendering your weight forever - Williamson, Marianne, 1952- (Carlsbad, Calif. : Hay House, 2010)
"21 spiritual lessons to help you surrender your weight forever. These lessons form a holistic paradigm for weight loss, addressing the spiritual, emotional, and psychological elements involved in what Willimason refers to as 'conscious weight loss. Addresses the true causal root of your weight-loss issues: a place within you where you have forgotten your Divine perfection. This forgetfulness has confused not only your mind but also your body .... As your mind reclaims its spiritual intelligence, your body will reclaim its natural inteligence as well ... A deep, sacred journey, ... you will learn to shift your relationship with yourself--and your body-- from one of fear to one of love."
Tear down the wall -- Thin you, meet not-thin you -- Build your altar -- Invoke the real you -- Start a love affair with food -- Build a relationship with good food -- Love your body -- Surrender to the divine -- Inhabit your body -- Consecrate your body -- Ritualize the change in you -- Commit to yourself -- Feel your feels -- Allow the pain -- Exit the alone zone -- Discipline and discipleship -- Forgive yourself and others -- Honor the process -- Birthing who you really are -- Soul surgery -- The body brilliant.
Keywords: Weight loss -- Psychological aspects; Weight loss -- Religious aspects -- Christianity